Negative correlation between leftward bias in line bisection and schizotypal features in healthy subjects - Ribolsi, Michele; Lisi, Giulia; Di Lorenzo, Giorgio; Rociola, Giuseppe; Niolu, Cinzia; Siracusano, Alberto (Frontiers in Psychology, 2013)
Abstract Introduction Recent studies have found a lack of normal pseudoneglect in schizophrenia patients and in their first degree relatives. Similarly, several contributions have reported that measures of schizotypy in the healthy population may be related to signs of right-sided lateralization, but most of these studies differ greatly in methodology (sample size, choice of schizotypy scales and laterality tasks) and, consequently, the results cannot be compared and so definitive conclusion cannot be drawn. In this study, our purpose is to investigate whether some tasks of spatial attention may be related to different dimensions of schizotypy not only in a larger sample of healthy subjects (HS), but testing the same people with several supposedly related measures several times. Materials and Methods In the first part of the study (Part I), the performance on “paper and pencil” line bisection (LB) tasks in 205 HS was investigated. Each task was repeated three times. In the second part of the study (Part II), a subgroup of 80 subjects performed a computerized version of the LB test and of the mental number line bisection (MNL) test. In both parts of the study, every subject completed the 74-item version of the Schizotypal Personality Questionnaire (SPQ) and the Edinburgh Handedness Inventory (EHI). Results In both parts of the study, high scores on the subscale "magical thinking" of SPQ have resulted in being closely linked to a decreased pseudoneglect as assessed by the LB task. On the contrary, right handedness is related to an increased leftward bias at the same task. No association was found between MNL and the other variables. Discussion The main finding of this study is that a decreased spatial leftward bias at the LB task correlates with positive schizotypy in the healthy population. This finding supports the hypothesis that a deviation from leftward hemispatial visual preference may be related to the degree of psychosis-like schizotypal signs in non-clini